2000
DOI: 10.1161/01.cir.101.8.917
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Changes in Myocardial Glucose Metabolism In Vivo During Reperfusion of a Limited-Duration Coronary Occlusion

Abstract: Background-Rapid reperfusion of an occluded coronary artery salvages regional mechanical function, but this benefit may not be realized for hours or days because of postischemic stunning. Recovery from stunning is incompletely understood but may involve adaptive changes in heart glucose metabolism. Methods and Results-To examine whether reversible coronary occlusion produces sustained changes in regional glucose metabolism in vivo, we performed a 20-minute left coronary artery occlusion followed by 24 hours of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 40 publications
3
44
0
2
Order By: Relevance
“…Nonetheless, these findings are supported by prior data in experimental animals and in human subjects, in which upregulation of glucose uptake by the ischemic myocardium was shown to persist for hours to days, even after a brief episode of ischemia (10,11).…”
Section: Persistent 18 F-fdg Uptake 24 H After Exercisesupporting
confidence: 76%
See 1 more Smart Citation
“…Nonetheless, these findings are supported by prior data in experimental animals and in human subjects, in which upregulation of glucose uptake by the ischemic myocardium was shown to persist for hours to days, even after a brief episode of ischemia (10,11).…”
Section: Persistent 18 F-fdg Uptake 24 H After Exercisesupporting
confidence: 76%
“…In the ischemic segment, the authors observed a fall in fatty acid use (assessed by 11 C-palmitate) and an increase in glycolytic flux (assessed by 18 F-FDG PET). Subsequent studies have demonstrated that enhanced exogenous glucose uptake may persist for 24 h or longer after a period of transient ischemia (10). In experimental studies, brief periods (3-5 min) of myocardial ischemia were shown to induce glucose transporter 4 sarcolemma translocation (13,14) and activate glycogen synthase.…”
Section: Experimental Evidence Of Metabolic Derangements After a Tranmentioning
confidence: 99%
“…With regard to cardiac ischemia, we (43) have shown that pretreatment of isolated hearts with ␣-tocotrienol, a vitamin E analog, preserves postischemic proteasome function. Although all of these studies support the notion that proteasome is sensitive to oxidative injury, it must not be forgotten that protein ubiquitination and unfolding are ATP dependent (77) and that during ischemia, ATP can be depleted (150,208) and thus may be a contributing factor.…”
Section: Proteasome Dysfunction In Myocardial Ischemiamentioning
confidence: 73%
“…U-13 C-Glucose was used to achieve measurable enrichment. Simultaneous ART and CS blood samples were obtained at 5,10,15,20,25,30,40,50, and 60 min after tracer administration for the measurement of 11 C-glucose, 11 CO 2 , and 11 C-lactate (12). Paired blood samples were also collected to determine plasma substrates (glucose, free fatty acids [FFA], lactate), and insulin at baseline, before 11 C injection and at 30 and 60 min of imaging.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Pert urbations in myocardial glucose metabolism occur in various diseases and states (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Thus, accurate measurements of myocardial glucose metabolism are necessary to better understand the physiology or pathophysiology of these processes and to evaluate novel therapies designed to ameliorate detrimental effects on cardiac function.…”
mentioning
confidence: 99%